Evaluation of tetrafunctional block copolymers as synthetic vectors for lung gene transfer. (March 2015) - Richard-Fiardo, Peggy; Hervouet, Catherine; Marsault, Robert; Franken, Philippe R.; Cambien, Béatrice; Guglielmi, Julien; Warnez-Soulie, Julie; Darcourt, Jacques; Pourcher, Thierry; Colombani, Thibault; Haudebourg, Thomas; Peuziat, Pauline; et al.
Abstract: In the present study, we evaluated, in mice, the efficacy of the tetrafunctional block copolymer 704 as a nonviral gene delivery vector to the lungs. SPECT/CT molecular imaging of gene expression, biochemical assays, and immunohistochemistry were used. Our dataset shows that the formulation 704 resulted in higher levels of reporter gene expression than the GL67A formulation currently being used in a clinical trial in cystic fibrosis patients. The inflammatory response associated with this gene transfer was lower than that induced by the GL67A formulation, and the 704 formulation was amenable to repeated administrations. The cell types transfected by the 704 formulation were type I and type II pneumocytes, and transgene expression could not be detected in macrophages. These results emphasize the relevance of the 704 formulation as a nonviral gene delivery vector for lung gene therapy. Further studies will be required to validate this vector in larger animals, in which the lungs are more similar to human lungs.